PENGARUH KEPEMIMPINAN DAN SANKSI PEKERJAAN TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. MEGA FINANCE CABANG MUARA BULIAN - Etty Siswati (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
The purpose of this study was to clarify the effect of leadership and disciplinary sanctions against employment of employees at PT. Mega Finance branch Muara Bulian . The analytical method used is quantitative tool which uses linear regression analysis . significant variables influence the leadership (X1) and Sanctions Work as an independ- ent variable, and Employee Discipline (Y) as the dependent variable done t test and test F. Results of hypothesis testing on Leadership variables influence the Employee Discipline that amounted to 10 531 t count > t table of numbers and figures a significance of 1.67866 (Sig) 0000 <) 0.05 (5%) with this it can beaon the level of significance seen that this leadership has influence on Employee Discipline. Results of testing hypotheses on variables sanctions work against Discipline Employee that the value t count equal to 3,605 and the significant level of 5% was obtained t table 1.67866 this case we can see that the value t calculate equal to 3,605> of the numbers t table 1.67866 and figures significance of (Sig ) 0001 <) 0.05 (5%) with this itaon the level of significance ( can be seen that the sanctions this work has an influence on Employee Discipline. Results of testing the hypothesis on the variables of leadership and disciplinary sanctions against employees' job directing that the value of F obtained F count with a significance level of 70 074 (0.000 < 0.05). F value table at 3.19 this means that F count (70 074 )> F table (3.1) thus ditolaktinya Ho and Ha accepted, meaning that leadership (X1) and Sanctions work (X2) has positive effect simultaneously or together Employee Discipline against the PT. Mega Finance branch Muarabulian Batang regency.Adjusted R Square generated at 0.738. So we can conclude percentage Leadership influence and Sanctions Against Public Employee Discipline in PT. Mega Finance Branch Muarabulian by 73.8% and 26.2% influenced other variables that are not researched in this study. Keyword: Leadership, Work Sanctions. Discipline Employee at PT. Mega Finance branch Muara Bulian.